2012
DOI: 10.1002/cncr.27624
|View full text |Cite
|
Sign up to set email alerts
|

Tumor response assessment by modified Choi criteria in localized high‐risk soft tissue sarcoma treated with chemotherapy

Abstract: BACKGROUND. The objective of this study was to compare the prognostic relevance of Response Evaluation Criteria in Solid Tumors (RECIST) versus Choi criteria for the assessment of response in patients with high-risk soft tissue sarcoma of the extremities or trunk wall who received preoperative chemotherapy with or without radiotherapy in a phase 3 trial. METHODS. Patients received 3 cycles of preoperative epirubicin þ ifosfamide with or without radiotherapy. The diagnostic concordance between RECIST and Choi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 43 publications
2
56
0
6
Order By: Relevance
“…In Table 3, an explorative analysis of the relation between the microscopic margin status and the risk of LR and DM in the subset of patients treated with preoperative CT only according to the response to the therapy is also reported. The responses were both classified according to RECIST and/or Choi criteria [26]. The results reported in this table are clearly meant to be explorative and hypothesis-generating.…”
Section: Local Recurrence and Distant Metastasesmentioning
confidence: 99%
“…In Table 3, an explorative analysis of the relation between the microscopic margin status and the risk of LR and DM in the subset of patients treated with preoperative CT only according to the response to the therapy is also reported. The responses were both classified according to RECIST and/or Choi criteria [26]. The results reported in this table are clearly meant to be explorative and hypothesis-generating.…”
Section: Local Recurrence and Distant Metastasesmentioning
confidence: 99%
“…This finding could be explained with reference to another substudy derived from the same trial. In this substudy, partial response was not able to anticipate better clinical outcome, RFS or OS, compared with stable disease according to RECIST criteria (36). Moreover, some progressive disease cases have been reported as complete pathologic response in the examination of surgical specimens.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have adopted 3D attenuation in order to improve upon the ability of RECIST to identify non-responders with localized high-risk soft-tissue sarcoma [13], locally advanced gastric cancer treated with cytotoxic drugs [14], or mRCC [15]. Smith et al [3], however, found that attention to tumour characteristics-e.g., necrosis on 2D images (morphology, attenuation, size, and structure [MASS] criteria)-was simpler and more accurate than 3D size and attenuation CT (SACT) measures for classifying responders versus non-responders.…”
Section: Discussionmentioning
confidence: 98%